Developments in Financial Supervision and the Use of Macroprudential Measures in Central America - Meza, Mynor; Delgado, Fernando (Washington, D.C. : International Monetary Fund, 2011)
Improvements in financial regulation and supervision in the Central American region (CAPDR) have strengthened financial stability. Prudential instruments with potential macroeconomic effects have been introduced. Nonetheless, compared with the larger Latin American and selected industrial countries, there is still important scope for CAPDR to enhance financial supervision and regulation. Based on two surveys, and the analysis of the Basel Core Principles, the paper determines that some weaknesses exist in risk-based supervision, and that macroprudential measures have scarcely been deployed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet